2018
DOI: 10.3390/rs10091341
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aquarius Sea Surface Salinity

Abstract: Abstract:Aquarius was the first NASA satellite to observe the sea surface salinity (SSS) over the global ocean. The mission successfully collected data from 25 August 2011 to 7 June 2015. The Aquarius project released its final version (Version-5) of the SSS data product in December 2017. The purpose of this paper is to summarize the validation results from the Aquarius Validation Data System (AVDS) and other statistical methods, and to provide a general view of the Aquarius SSS quality to the users. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 22 publications
(31 reference statements)
2
61
0
Order By: Relevance
“…Before the application of satellite‐retrieved salinity data, the calibration and validation of the satellite SSS were a guarantee of data accuracy and the fidelity of the research findings. Previous studies conducted salinity data quality assessments by comparing satellite SSS with in situ measurements, but mainly for SMOS and Aquarius satellite data products (Garcia‐Eidell et al, ; Kao, Lagerloef, Lee, Melnichenko, Meissner, et al, ; Köhler et al, ; Lee, ; Maqueda et al, ; Reagan et al, ; SMOS‐BEC Team, ; Tang et al, ). Due to the late launch of the SMAP satellite, there are few related studies (Meissner et al, ; W. Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Before the application of satellite‐retrieved salinity data, the calibration and validation of the satellite SSS were a guarantee of data accuracy and the fidelity of the research findings. Previous studies conducted salinity data quality assessments by comparing satellite SSS with in situ measurements, but mainly for SMOS and Aquarius satellite data products (Garcia‐Eidell et al, ; Kao, Lagerloef, Lee, Melnichenko, Meissner, et al, ; Köhler et al, ; Lee, ; Maqueda et al, ; Reagan et al, ; SMOS‐BEC Team, ; Tang et al, ). Due to the late launch of the SMAP satellite, there are few related studies (Meissner et al, ; W. Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The remotely sensed OWS are primarily derived from scatterometer observations (i.e., active microwave observations), but the dual polarization microwave radiometer measurements also provide valuable wind speed estimates, especially at high wind speed (above ∼15 m/s; Reul et al, ) where scatterometer measurements tend to saturate (Quilfen et al, ). SSS estimates have only been possible since the advent of satellite L‐band measurements (1.4 GHz) from the Soil Moisture and Ocean Salinity mission (SMOS; since 2009), Aquarius, and now the Soil Moisture Active and Passive mission (SMAP; Boutin et al, ; Fore et al, ; Kao et al, ; Lagerloef et al, ; Le Vine et al, ; Meissner et al, ; Reul et al, ). When averaged over 1 week, the precision on the satellite salinity over the open ocean is typically 0.2 psu (Boutin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we let k 1 = 0.16 and k 2 = 2500. The value of x qual was determined using Equation (10). Then, the gridded SSS values with distance weighting were obtained for different values of k 3 .…”
Section: Interpolation Methodsmentioning
confidence: 99%
“…To assess and validate the accuracy of the Aquarius gridded SSS fields, tests have been conducted in both global oceans and regional basins [6][7][8][9]. Official Aquarius version 5.0 products have been published, and the accuracy of the monthly L3 1 • SSS fields has been estimated via a triple point analysis using individual matchups among Aquarius data, Argo float data and Hybrid Coordinate Ocean Model (HYCOM) data [10,11]. The triple point analysis results showed that the monthly average RMSD of the Aquarius L3 field data was 0.128 psu, whereas the mean RMSD between the weekly The Aquarius SSS L2 (version 5.0) products from September 2011 to May 2015 are used in this paper.…”
Section: Introductionmentioning
confidence: 99%